Promoter attenuation in gene therapy: interferon-gamma and tumor necrosis factor-alpha inhibit transgene expression - Qin, L; Ding, Y; Pahud, D R; Chang, E; Imperiale, M J; Bromberg, J S (Human gene therapy, 1997)
One of the major limitations to current gene therapy is the low-level and transient vector gene expression due to poorly defined mechanisms, possibly including promoter attenuation or extinction. Because the application of gene therapy vectors in vivo induces cytokine production through specific or nonspecific immune responses, we hypothesized that cytokine-mediated signals may alter vector gene expression. Our data indicate that the cytokines interferon-gamma (IFN-gamma) and tumor necrosis factor-alpha (TNF-alpha) inhibit transgene expression from certain widely used viral promoters/enhancers (cytomegalovirus, Rous sarcoma virus, simian virus 40, Moloney murine leukemia virus long terminal repeat) delivered by adenoviral, retroviral or plasmid vectors in vitro. A constitutive cellular promoter (beta-actin) is less sensitive to these cytokine effects. Inhibition is at the mRNA level and cytokines do not cause vector DNA degradation, inhibit total cellular protein synthesis, or kill infected/transfected cells. Administration of neutralizing anti-IFN-gamma monoclonal antibody results in enhanced transgene expression in vivo. Thus, standard gene therapy vectors in current use may be improved by altering cytokine-responsive regulatory elements. Determination of the mechanisms involved in cytokine-regulated vector gene expression may improve the understanding of the cellular disposition of vectors for gene transfer and gene therapy.